Z czerwonym Kielichem. Przedmiot wiary husytów w Trylogii husyckiej Otokara Vavry. - Łazarz, Radosław (Slavia Occidentalis, 2016)
The study is dedicated to Otokar Vavra’s cinematographic “Hussites Revolutionary Trilogy”. The films were shot in the 1950s as colour motion pictures. The main idea is based on Alois Jirasek’s trilogy and Frantisek Palacky’s philosophy of history combined with some ideological concepts revolving around the communist interpretation of Hussites. The three films: Jan Hus (1954), Jan Žižka (1955) and Proti všem (Against All Odds, 1957) pose some sort of a challenge by showing a religious movement from an atheist’s perspective. Vavra indeed created a work of propaganda, a heroic story of the Czech folk fighting against foreign powers (lords and nobles, crusaders) which had the potential of underpinning the communist ideology in Czechoslovakia. On the other hand, the trilogy took in a new symbolic meaning after the 1968 occupation by the Warsaw Pact.